2018
DOI: 10.1039/c8cp05533e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and simulation of V-shaped Ag nanorods as high-performance SERS substrates

Abstract: V-shaped AgNRs have a higher SERS sensitivity than straight AgNRs and their resonance wavelengths can be tuned linearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Typically, after the fabrication of the first arm followed by a short cooling, the substrates holder was azimuthally rotated a certain angle to start deposition of the next arm. The numerical simulation was employed to compare EFs of V-shape and straight AgNRs with the same length, and the result (Figure 2B) showed that V-shape AgNRs exhibited stronger EFs in almost 90% cases under a 785 nm laser (Li et al, 2018). SERS performance of AgNRs as a function of the arm number N ( N ≥ 3) was also investigated.…”
Section: Synthesis and Properties Of Agnrs-based Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, after the fabrication of the first arm followed by a short cooling, the substrates holder was azimuthally rotated a certain angle to start deposition of the next arm. The numerical simulation was employed to compare EFs of V-shape and straight AgNRs with the same length, and the result (Figure 2B) showed that V-shape AgNRs exhibited stronger EFs in almost 90% cases under a 785 nm laser (Li et al, 2018). SERS performance of AgNRs as a function of the arm number N ( N ≥ 3) was also investigated.…”
Section: Synthesis and Properties Of Agnrs-based Nanostructuresmentioning
confidence: 99%
“…(B) Numerical simulations of Raman EFs for the V-shaped AgNR and the straight AgNR as a function of AgNRs total length under a 785 nm laser. Reproduced with permission from Li et al (2018). Copyright (2018) RSC publications.…”
Section: Synthesis and Properties Of Agnrs-based Nanostructuresmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) has been emerging as a powerful spectroscopic technique due to its extremely high sensitivity, fingerprint character and rapid nondestructive detection of molecules at an ultralow concentration [1][2][3][4][5]. In general, local surface plasmon resonance preferentially occurs in the nanoscale gaps between metal nanostructures [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work revealed that V-shaped Ag NR arrays possess much better SERS sensitivity than straight Ag NRs by building implanted hot spots within individual nanorods. 14 Normally, the hot spots could be observed at the junctions of nanodimers or on the tips of nanostructures. In this work, we successfully fabricated a series of armrest Ag NRs@Al 2 O 3 with well-controlled morphology as well as enhanced hot spots quantity by taking advantage of the AAO template and oblique angle deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, localized surface plasmon resonance (LSPR) and the related physical phenomenon have received tremendous research attention due to the extensive optical manipulation and utilization of sensor applications in surface science. With the successful establishment of a nanostructure where local electric field intensity enhanced significantly (10 4 –10 9 enlarged magnitudes), LSPR enhancement is considered to be effective in near-field manipulation upon illumination and induces remarkable surface-enhanced Raman scattering (SERS). As has been widely demonstrated, the excitation and modulation of LSPR are not only related to the dielectric constant of the selected materials or the surrounding environment but also greatly dependent on the morphology, structure, and interparticle coupling of the nanostructures. To effectively enlarge the LSPR enhancement degree, and thus gain outstanding SERS performance, researchers have put great efforts in designing nanostructures with enhanced intensified electromagnetic fields, that is, the “hot spots”. Generally, the more the hot spots in the micronanostructure, the stronger the SERS signal generated from the substrate. In addition, the reduction of spacing between the adjacent structures and the ratio of the interparticle gap to the diameter could significantly enhance the local hot spots intensity of the SERS-active substrate, endowing further enhanced performance of the nanostructure with given hot spots quantity.…”
Section: Introductionmentioning
confidence: 99%